PTU-169 Long-lasting Oesophageal Mucosal Protction With Alginates: A Potential For Topical Mucosal Therapy In Gastro-oesophageal Reflux. (9th June 2014) - Woodland, P; Lee, C; Dettmar, P; Preston, SL; Sifrim, D
Abstract : Introduction: Patients with non-erosive reflux disease (NERD) exhibit impaired oesophageal mucosal barrier integrity in the form of dilated intercellular spaces and low transepithelial electrical resistance (TER). Such refluxate-induced changes to the mucosal integrity may underlie increased sensitivity to perception of reflux events, even on PPI, and could potentially be modified by application of topical solutions. Sodium alginate solutions are used in treatment of GORD, with proposed mechanisms of action including acid buffering, displacement of the gastric acid pocket, and reduction of reflux events. We have recently described that in vitro topical application of a sodium alginate solution is able to protect mucosal biopsies against impairment of oesophageal mucosal integrity when exposed to acidic solutions shortly after application. The durability of this protection is unclear. We aimed to assess the protective effect and physical location of a topically applied sodium alginate solution 1 h after application. Methods: 3 mucosal biopsies were taken from the distal oesophagus (3 cm above the z-line) in 10 patients attending the Royal London Hospital for gastroscopy. Biopsies were transferred immediately to Krebs buffer pH 7.4. The luminal surfaces of 2 biopsies were coated with 200 µl of either a sodium alginate solution (Gaviscon Advance, Reckitt Benckiser, Hull, UK) or a viscous control solution (of same viscosity, but without alginate). The biopsies were mechanically washed with 5 ml Krebs, then each placed in an Using chambers and bathed in pH 7.4 solution for 1 h. The luminal aspect of the biopsy was then exposed for 30 min to an acidic solution pH 2 + 1 mg/ml pepsin + 1 mM taurodeoxycholate. Percentage changes in TER from baseline at the end of exposure were recorded. For the 3 rd biopsy sodium alginate solution containing fluorescein-labelled alginate was used, and after 1 h bathing in pH 7.4 solution the biopsy was fixed for immunohistological detection of the alginate. Results: Our previous experiments have demonstrated that exposure of unprotected biopsies to the acidic solution results in a –14.4 ± 2.9% change in TER from baseline. 1 h after protection with alginate solution the same exposure caused a –8.2 ± 4.2% change in TER compared to –15.9 ± 3.0% change after protection with the viscous control (p < 0.05). Labelled alginate could be seen coating the luminal surface after 1 h in all cases. Conclusion: In vitro, alginate solutions can adhere to the oesophageal mucosa for up to 1 h and exert a topical protectant effect against refluxate-like solutions. This suggests that durable topical protectants can be further explored and developed as first-line/add-on therapies for GORD. Disclosure of Interest: P. Woodland: None Declared, C. Lee: None Declared, P. Dettmar Employee of: Technostics Limited, S. Preston: None Declared, D. Sifrim Grant/research support from: Reckitt-Benckiser, Sandhill Scientific, Consultant for: Sandhill Scientific.